Diagnosis and Treatment of Infant Botulism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The clinical presentation, diagnosis, and treatment of infant botulism (IB) are reviewed by investigators at the University of California-San Francisco, CA.